Are comprehensive environmental changes as effective as health education for smoking cessation?. Issue 1 (24th January 2006) - Kadowaki, T; Kanda, H; Watanabe, M; Okayama, A; Miyamatsu, N; Okamura, T; Hayakawa, T; Hishida, K; Kita, Y; Ueshima, H
Abstract : Objectives: To compare the effectiveness of health education on smoking cessation for all smokers regardless of their willingness to quit smoking and cumulative environmental changes including designation of smoking places, legislation, and price rise. Design: Comparison of smoking cessation rates over two time periods: the period of health education on smoking cessation (1997–1999), and the period of cumulative environmental changes (2002–2004). Setting: An occupational setting in a radiator manufacturing factory in Japan. Subjects: All habitual male smokers who remained in the worksite through the pertinent time period (n  =  202 in the period of health education and n  =  170 in the period of environmental changes). Main outcome measurements: Smoking cessation rates at the end of each time period. Results: The smoking cessation rates over the periods of health education and environmental changes were 8.9% and 7.1%, respectively. There was no difference between these two proportions in a χ 2 test (p  =  0.513). The age adjustment did not significantly alter the cessation rate. Conclusions: Cumulative environmental changes are fairly effective in promoting smoking cessation, and may yield similar smoking cessation rates as a health education intervention reaching all smokers regardless of their willingness to quit smoking.